Effectiveness of Income Tax Revenue Article 23 at the Fort Selayar Islands Tax Counseling & Consultation Services Office - Wahyudi Nasar Putra (JEKAMI Journal of Accounting, 2023)
This research by Wahyudi Nasar Putra from the University of Muhammadiyah Makassar investigates the effectiveness of implementing Income Tax Article 23 at the Benteng Selayar Islands Tax Counseling and Consultation Services Office. Utilizing qualitative methods, the study employs interviews and observations for data collection. Findings reveal that the calculation of Income Tax Article 23 has not been executed effectively in accordance with the Income Tax Law. The introduction highlights Indonesia's development challenges and the pivotal role of tax collection in achieving economic stability. The self-assessment tax system is discussed, emphasizing the importance of tax administration, counseling, and consultation services, particularly at the Benteng Selayar Islands office. Research methods involve a two-month study period, using interviews, observations, and documentation analysis. Results indicate varying effectiveness levels over the years (2020-2022), with 2020 being effective (87.88%), 2021 less effective (37.55%), and 2022 very ineffective (11.26%), attributed to the Covid-19 pandemic. Discussion focuses on challenges faced by the tax office, emphasizing the importance of routine inspections and strengthened supervision. The study aligns with previous research and offers recommendations for increased supervision and audits to enhance the accuracy and effectiveness of Income Tax Article 23 calculations and reporting. In conclusion, the research provides insights into the challenges faced by the Benteng Selayar Islands Tax Counseling and Consultation Services Office, proposing practical recommendations for improvement.